Investigating the impacts of digital finance technology on financial stability of the banking sector: New insights from developing market economies - Frank Antwi; Yusheng Kong (Cogent Business & Management, 2023)
This study investigates the effects of digital finance technology, i.e., mobile phones and internet usage on financial stability of the banking sector in developing market economies. We used data from 2000 to 2020 from 55 selected developing economies to examine the link between digital finance technology and financial stability. According to the empirical results from the quantile regression, mobile phone subscriptions as a proxy for digital finance technology has a negative impact on the financial stability of the chosen emerging economies. In contrast, the findings indicate that internet usage as a proxy for digital finance technology has a favorable impact on the financial stability (FS) of developing economies. Given that digital finance technology has a variety of implications on the financial stability of emerging countries, the study advises policymakers to assess current digital finance technology (internet usage and mobile phone subscription) and banking-related regulations and align them with various aspects of financial stability.
Keywords: 650; developing markets; digital finance technology; financial stability; Internet usage; mobile phones; moment of quantile regression method